On Women’s Shoulders: Care-Based Immobility and Climate Adaptation in Rural Ghana - Boldrini, Mariachiara; Saggiomo, Valeria (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2026)
This article examines the gendered dynamics of climate-related migration and immobility in rural Ghana, focusing on the Bono and Bono East regions. Drawing on ethnographic fieldwork conducted between 2022 and 2023, it explores how male out-migration, often framed as an adaptive response to environmental stress, reshapes the gendered distribution of labor, women’s responsibilities, and their opportunities for mobility. The study introduces the concept of care-based immobility as a central analytical contribution. It conceptualizes women’s staying as a socially produced condition rooted in three interrelated domains—economic management, food security, and caregiving. These responsibilities simultaneously anchor women geographically while enabling household and community survival, demonstrating that immobility operates as both a structural constraint and an active strategy of climate adaptation. By integrating feminist political ecology with critical mobility and immobility frameworks, the analysis moves beyond environmentally deterministic narratives of climate migration and situates women’s (im)mobility within relational socio-ecological hierarchies. The article thus underscores the importance of gender-sensitive and locally grounded approaches to climate resilience.